Addressing health disparities as a function of ethnicity in systemic lupus erythematosus patients. (December 2022) - González, Luis A; Ugarte-Gil, Manuel F; Pons-Estel, Guillermo J; Durán-Barragán, Sergio; Toloza, Sergio; Burgos, Paula I; Bertoli, Ana; Borgia, R Ezequiel; Alarcón, Graciela S
Systemic lupus erythematosus (SLE) is an autoimmune disorder with significant health disparities, as it disproportionately and more severely affects vulnerable and disadvantaged population groups in the United States and around the world, that is, women, ethnic minorities, individuals living in poverty, less educated, and lacking medical insurance. Both, genetic and non-genetic factors, contribute to these disparities. To overcome these health disparities and reduce poor outcomes among disadvantaged SLE populations, interventions on non-genetic amendable factors, especially on social health determinants, are necessary.